Draft Annual Plan, 2011-12 Volume II Statement I To XXVI (Except VII To X) Statement III In Supplement of Volume II - Planning Commission (Planning Commission, 2011)
A Summary Statement of Major Headwise - Outlays and Expenditure, STATEMENT IB Summary Statement of Sub-Major Headwise - Outlays and Expenditure, Physical Targets & Achievements, A Externally Aided Projects - Outlays and Expenditure, Externally Aided Projects - Physical Targets and Achievements, Bharat Nirman Programme - Outlays and Expenditure, Centrally Sponsored Schemes - Outlays and Expenditure, Voluntary Sector - Outlays and Expenditure, Women Component (WC) - Outlays and Expenditure, Women Component (WC) - Physical Targets and Achievements
Statement I To XXVI (Except VII To X) Statement III In Supplement of Volume II